Activating Mutations Affecting the Dbl Homology Domain of SOS2 Cause Noonan Syndrome. Issue 11 (3rd August 2015) - Cordeddu, Viviana; Yin, Jiani C.; Gunnarsson, Cecilia; Virtanen, Carl; Drunat, Séverine; Lepri, Francesca; De Luca, Alessandro; Rossi, Cesare; Ciolfi, Andrea; Pugh, Trevor J.; Bruselles, Alessandro; Priest, James R.; et al.
<x xml:space="preserve">Abstract</x> Noonan syndrome‐causing mutations alter the Dbl homology domain (DH, shown as ribbon), altering its interaction with the RAS exchange motif, colored by its electrostatic potential. The mutated residue in the DH domain are colored red.